PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Ardalia Theodore; Besti Lilyana (Jurnal Bisnis Darmajaya, 2017)
This study aims to determine how much influence compensation and job satisfaction on employee performance at PT. Mandir Utama's Advanced Works. This research type is quantitative research and uses associative method, Data used is primary data. Based on the results of this study, obtained value R2 (R Square) of 0.617, it shows that Employee Performance (Y) is influenced by Compensation (X1), and Job Satisfaction (X2) of 61.7%, while the remaining 38.3% By another factor. Based on the results of multiple linear regression tests for hypothesis testing partially resulted there is influence Compensation (X1) on Employee Performance (Y) at PT. Karya Canggih Mandirutama, and there is an influence of Job Satisfaction (X2) on Employee Performance (Y) at PT. Mandir Utama's Advanced Works. Hypothesis testing simultaneously resulted in the influence of Compensation (X1), and Job Satisfaction (X2) on Employee Performance (Y) at PT. Mandir Utama's Advanced Works. Keywords: Compensation, Job Satisfaction, Employee Performance.